![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1
2(\(\frac{3}{4}\)-5x)=\(\frac{4}{5}\)-3x
=> \(\frac{6}{4}-10x=\frac{4}{5}-3x\)
=>\(-10x+3x=\frac{4}{5}-\frac{6}{4}\)
=> \(x=\frac{1}{10}\)
2 .
\(\frac{3}{2}-4\left(\frac{1}{4}-x\right)=\frac{2}{3}-7x\)
=>\(\frac{3}{2}-1+4x=\frac{2}{3}-7x\)
=>\(11x=\frac{1}{6}\)
=>x=\(\frac{1}{66}\)
3.
\(3\left(\frac{1}{2}-x\right)+\frac{1}{3}=\frac{7}{6}-x\)
=>\(\frac{3}{2}-3x+\frac{1}{3}=\frac{7}{6}-x\)
=>\(-2x=\frac{-2}{3}\)
=>\(\frac{1}{3}\)
4. câu 4 ko hiểu bạn ơi
![](https://rs.olm.vn/images/avt/0.png?1311)
b) \(\left(5x-1\right)\left(2x-\frac{1}{3}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}5x-1=0\\2x-\frac{1}{3}=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}5x=1\\2x=\frac{1}{3}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{1}{5}\\x=\frac{1}{6}\end{matrix}\right.\)
e, \(-\frac{3}{4}-\left|\frac{4}{5}-x\right|=-1\)
\(\Leftrightarrow\left|\frac{4}{5}-x\right|=-\frac{3}{4}-\left(-1\right)\)
\(\Leftrightarrow\left|\frac{4}{5}-x\right|=\frac{1}{4}\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{4}{5}-x=\frac{1}{4}\\\frac{4}{5}-x=-\frac{1}{4}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{7}{15}\\x=1,05\end{matrix}\right.\)
Vậy ....
![](https://rs.olm.vn/images/avt/0.png?1311)
1)\(-\frac{3}{2}\left(\frac{4}{5}-\frac{2}{3}\right)+x=4\left(x-\frac{2}{3}\right)\)
\(\Leftrightarrow-\frac{3}{2}\cdot\frac{2}{15}+x=4x-\frac{8}{3}\)
\(\Leftrightarrow-\frac{1}{5}+x=4x-\frac{8}{3}\)
\(\Leftrightarrow x-4x=-\frac{8}{3}+\frac{1}{5}\)
\(\Leftrightarrow-3x=-\frac{37}{15}\)
\(\Leftrightarrow x=\frac{37}{45}\)
2)\(2\left(\frac{3}{2}-x\right)-\frac{1}{3}=7x-\frac{1}{4}\)
\(\Leftrightarrow3-2x-\frac{1}{3}=7x-\frac{1}{4}\)
\(\Leftrightarrow-2x-7x=-\frac{1}{4}-3+\frac{1}{3}\)
\(\Leftrightarrow-9x=-\frac{35}{12}\)
\(\Leftrightarrow x=\frac{35}{108}\)
3)\(\frac{1}{5}\left(-\frac{3}{5}10\right)+5x=x-\frac{2}{3}\)
\(\Leftrightarrow-\frac{6}{5}+5x=x-\frac{2}{3}\)
\(\Leftrightarrow5x-x=-\frac{2}{3}+\frac{6}{5}\)
\(\Leftrightarrow4x=\frac{8}{15}\)
\(\Leftrightarrow x=\frac{2}{15}\)
4)\(-\frac{3}{2}\left(5-\frac{1}{6}\right)+4\left(x-\frac{1}{2}\right)=1\)
\(\Leftrightarrow-\frac{15}{2}+\frac{1}{4}+4x-2=1\)
\(\Leftrightarrow4x=1+\frac{15}{2}-\frac{1}{4}+2\)
\(\Leftrightarrow4x=\frac{41}{4}\)
\(\Leftrightarrow x=\frac{41}{16}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1,\(2\left(\frac{3}{4}-5x\right)=\frac{4}{5}-3x\)
\(\frac{6}{4}-10x=\frac{4}{5}-3x\)
\(\frac{6}{4}+\frac{4}{5}=7x\)
\(\frac{23}{10}=7x\)
\(\frac{23}{70}=x\)
2,\(\frac{3}{2}-4\left(\frac{1}{4}-x\right)=\frac{2}{3}-7x\)
\(\frac{3}{2}-1-4x=\frac{2}{3}-7x\)
\(\frac{3}{2}-1-\frac{2}{3}=-3x\)
\(\frac{-1}{6}=-3x\)
\(\frac{1}{18}=x\)
3,\(3\left(\frac{1}{2}-x\right)+\frac{1}{3}=\frac{7}{6}-x\)
\(\frac{3}{2}-3x+\frac{1}{3}=\frac{7}{6}-x\)
\(\frac{3}{2}-\frac{7}{6}+\frac{1}{3}=2x\)
\(\frac{2}{3}=2x\)
\(\frac{1}{3}=x\)
4,mình không hiểu a ở đây là gì
(5x-1)^3=-1/8
5x-1 = -1/2
5x= -1/2+1
5x = 1/2
x=1/2.1/5
x=1/10
Vậy x=1/10
(5x-1)3 = (-1/2)3
<=>5x-1=-1/2
<=>x=1/10